2021
DOI: 10.1111/adj.12818
|View full text |Cite
|
Sign up to set email alerts
|

What should every dental health professional know about electronic cigarettes?

Abstract: Electronic cigarettes (E‐cigarettes) have become increasingly popular around the world. Currently, dental professionals’ knowledge and attitudes are varied with many clinicians unclear regarding the impact of E‐cigarette products on the oral and general health of their patients. With developing social and health‐related challenges, advice of dental and medical associations and other regulatory bodies on E‐cigarette use is changing. Growing evidence demonstrating the risks of E‐cigarette usage has prompted a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 76 publications
1
9
0
4
Order By: Relevance
“…The largest volume of primary literature on the effects of e‐cigs on the upper aerodigestive tract is in relation to oral and dental health. 26 , 27 , 28 , 29 , 166 , 167 , 168 , 169 As expected, e‐cigs do not appear to be as harmful as conventional cigarette smoke in cell and animal models. 170 , 171 Nevertheless, numerous studies have demonstrated biological disruption as a result of even brief e‐cig exposure.…”
Section: Discussionsupporting
confidence: 71%
“…The largest volume of primary literature on the effects of e‐cigs on the upper aerodigestive tract is in relation to oral and dental health. 26 , 27 , 28 , 29 , 166 , 167 , 168 , 169 As expected, e‐cigs do not appear to be as harmful as conventional cigarette smoke in cell and animal models. 170 , 171 Nevertheless, numerous studies have demonstrated biological disruption as a result of even brief e‐cig exposure.…”
Section: Discussionsupporting
confidence: 71%
“…Driven by the critical importance of having a high level of knowledge on E-cigarettes, Briggs et al, after surveying dental professionals, dental associations, and regulatory authorities, presented updated information about E-cigarettes, its harmful effects, counseling advice, and proposed regulations [ 42 ]. The internet, represented mostly by social media, is unsurprisingly the main source of information about many daily matters, including E-cigarettes (33%), while dental schools paradoxically do not contribute more than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Como já mencionado, a exposição das células do epitélio oral ao vapor de cigarro eletrônico aumenta o estresse oxidativo e a liberação de citocinas pró-inflamatórias. Dessa maneira, estes eventos ocasionam efeitos na boca e na garganta, aumentando a probabilidade de câncer oral, sendo eles: xerostomia, secura, irritação, sensibilidade, queimação, lesões na mucosa oral, queimadura, estomatite nicotínica, língua pilosa, ardor, mau hálito, língua escurecida, quelite, atraso de cicatrização e hematoma labial, além de leucoplasia e carcinoma de células escamosas (Briggs;Bell;Breik, 2021;Ebersole, 2020, Lima Menezes Et al., 2021, Sultan Et al., 2021Yang;Sandeep;Rodriguez, 2020).…”
Section: Resultsunclassified
“…Outro ponto é que o uso excessivo dos cigarros eletrônicos implica de forma negativa na estética e anatomia dental, gerando dentes rachados, descoloração do esmalte, alteração na luminosidade e translucidez deste, dor, sensibilidade e presença de abcesso. Outrossim, os autores também apontam relatos de incidentes de lesões, traumas e avulsões ocasionadas por superaquecimento, incêndio e explosões de cigarros eletrônicos, induzindo queimaduras labiais, indução crônica de câncer nasossinusal e pulmonar (Briggs;Bell;Breik, 2021;Javed Et al., 2017;Roubahia, 2020;Vohra Et al., 2020;Yang;Sandeep;Rodriguez, 2020).…”
Section: Resultsunclassified
See 1 more Smart Citation